Efektivitas Pembelajaran Problem Solving Terhadap Kemampuan Pemecahan Masalah Matematis Ditinjau dari Motivasi Belajar Siswa (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to describe the success of the Problem Solving model in improving students' mathematical problem-solving skills from the perspective of learning motivation. This study uses a sequential explanator design. The research sample consisted of 36 students of SMP Negeri 3 Darma for the 2023/2024 academic year, namely 18 VIII A students as the experimental group and 18 VIII B students as the control group. The instruments used are tests and questionnaires. Data analysis was carried out using 2-Path Variance Analysis. The results of the data analysis were known with a significance level of 5% that in the learning model factor, a value of 0.000 < 0.05 was obtained with the conclusion that there was a difference in mathematical problem-solving ability between students who were given Problem Solving learning and conventional learning. Hypothesis testing of learning motivation factors had a value of 0.307 > 0.05 with the conclusion that there was no difference in mathematical problem-solving ability between students and High, medium, and low learning motivation